Evidence of validity for the Student Stress Scale for Brazilian university students - Taborda de Souza Filho, Paulo Roberto (2020)
This study shows the evidence of validity of the Student Stress Scale for Brazilians. It was administered to 585 Brazilian students. Factor Analyses demonstrated the existence of four factors, with high internal consistency indicators (physiological symptoms: ?=.82, professor-student relationship: ?=.80, inability and inferiority: ?=.77 and leisure: ?=.75) and good model fit indexes: x²=282.313 (p=.00); x²/gl=1.73; TLI=.97; RMSEA=.05 (I.C.=.04–.06); CFI=.97. Pearson Correlation analysis showed good correlation coefficients for the gold-standard criteria (Perceived Stress Scale; r=.60, p?.01) and good indexes for sensibility (99.2%) and specificity (89.6%). Results indicate that the scale can contribute to new research on academic stress in university students.